2020
DOI: 10.1111/btp.12754
|View full text |Cite
|
Sign up to set email alerts
|

Termite mounds house a diversity of taxa in oil palm plantations irrespective of understory management

Abstract: We investigated the effects of oil palm understory vegetation management on termite mound activity and non‐termite inhabitants. We found a diversity of taxa, most of which were unaffected by understory management. Mound volume and termite activity had taxa‐specific effects on abundance. Preserving mounds in oil palm plantations will benefit biodiversity. Abstract in Indonesian is available with online material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 46 publications
(62 reference statements)
0
3
0
Order By: Relevance
“…With such effective digestion, termites emit significant amounts of methane and carbon dioxide into the atmosphere (Sanderson, 1996). Some termite species build soil nests and protective structures, thereby substantially contributing to soil bioturbation and by nest space provisioning to soil biodiversity (Visser, Freymann & Schnyder, 2008; Hood et al ., 2020).…”
Section: Synopsis Of Feeding Habitsmentioning
confidence: 99%
See 1 more Smart Citation
“…With such effective digestion, termites emit significant amounts of methane and carbon dioxide into the atmosphere (Sanderson, 1996). Some termite species build soil nests and protective structures, thereby substantially contributing to soil bioturbation and by nest space provisioning to soil biodiversity (Visser, Freymann & Schnyder, 2008; Hood et al ., 2020).…”
Section: Synopsis Of Feeding Habitsmentioning
confidence: 99%
“…A range of lizards, birds and invertebrates also attack termites (Deligne et al, 1981;Pianka, 1986). However, the most important termite predators are ants (Hölldobler & Wilson, 1990). There are both generalist termite-preying ants such as Pheidole spp., and highly specialised species able to disrupt termite colonies such as Neoponera spp.…”
Section: (D) Chilopodamentioning
confidence: 99%
“…Previous studies have shown that maintaining heterogeneity in oil palm landscapes can improve the biodiversity and structural complexity of plants (Luke et al, 2019a), and the abundance or biodiversity of a wide range of invertebrate and vertebrate taxa, including birds (Teuscher et al, 2016;Yahya et al, 2017), bats (Syafiq et al, 2016), soil invertebrates (Ashton-Butt et al, 2018), and leopard cats (Hood et al, 2019). Additionally, as arthropods influence existing trophic networks in oil palm systems (Barnes et al, 2014), and otherwise interact ecologically with non-arthropod groups (for instance, termite mounds are valuable nesting sites for snakes in oil palm plantations; Hood et al, 2020b), differences in arthropod biodiversity between buffer and non-buffer areas could affect the biodiversity of non-arthropod biota. Future studies are needed to determine the impacts of mature palm buffers on non-arthropod taxonomic groups, and potential knock-on effects on ecosystem functioning.…”
Section: Differences Between Mature Palm Buffers and Surrounding Habi...mentioning
confidence: 99%